Consumption trends and prescription patterns of opioids from 2011 to 2016: a survey in a Chinese city. Issue 3 (1st March 2019) - Liu, Xiao; Luo, Can; Dai, Huizhen; Fang, Wentong
Abstract : Objective: Opioid consumption in China has been very less and has varied widely since 1995. The representatively high level of consumption in Mainland China has never been reported. Our aim was to describe the consumption trends and prescription patterns of opioids in Nanjing, a highly developed city of Mainland China, and compare the results with selected worldwide regions. Methods: Application data of opioids in 2011–2016 were extracted from the Jiangsu Medicine Information Institute. Six opioids were included. Consumption was expressed in terms of defined daily doses (DDDs), morphine equivalents (MEs) and expenditure. The correlation between consumption of opioids and gross domestic product (GDP), Human Development Index (HDI) and cancer incidence was analysed by Pearson's correlation test. Results: DDDs, expenditure and MEs of opioids were, respectively, 256.04, 599.24 and 13.07 g in 2011, and increased to 361.27, 1041.79 and 18.09 g in 2016. DDDs in Nanjing were 2.80-fold that in Mainland China, 1.42-fold that in East and South-East Asia, but only equivalent to 8.89% of the worldwide average level. From 2011 to 2016, the consumption had a linear correlation with GDP, HDI and cancer incidence (p<0.05). However, DDDs varied greatly in countries with similar GDP or HDI. Within 45 Asian countries, the GDP only contributed to 10.47% of change in DDDs, while the HDI contributed to 20.32%. Consumption of non-intravenous opioids or strong opioids always comprised majority of the total consumption. The opioids prescribed predominantly were fentanyl, oxycodone and morphine. Fentanyl and oxycodone account for most of the increase in consumption. Conclusion: Opioid consumption has increased >40% from 2011 to 2016, with consumption of fentanyl and oxycodone accounting for most of that increase. The consumption in Nanjing was higher than the average Chinese level, but lower than the global average. An increase in pain control services might be needed, but this need should be highly regulated.